Bloodstream infection caused by Erysipelothrix rhusiopathiae serotype 6: Case report and literature review - Asumi Suzuki; Mariko Hakamata; Syunya Tanikawa; Naoto Kanno; Ikumi Yamagishi; Masahiro Ui; Hayato Tsuruma; Yuuki Bamba; Hideyuki Ogata; Satoshi Shibata; Hiromi Cho; Mizuho Sato; et al. (IDCases, 2025)
Erysipelothrix rhusiopathiae is a zoonotic, facultatively anaerobic, non-spore-forming, gram-positive bacillus. Although the serotypes and phylogenetic clades of E. rhusiopathiae strains isolated from animals have been shown to be closely related, the serotype identification of clinical isolates from human patients remains limited. We report a case of a 66-year-old woman with bacteremia caused by E. rhusiopathiae serotype 6. The patient had been admitted with aspiration pneumonia and heat stroke. She had no animal-related occupational history and had been receiving long-term oral prednisolone therapy for mixed connective tissue disease. Upon confirmation of E. rhusiopathiae positivity on blood cultures, she was treated with intravenous ampicillin for 10 days and achieved complete recovery. Agar gel precipitation and polymerase chain reaction tests identified the isolate as serotype 6. Surface protective antigen (Spa) typing by sequence analysis suggested a marine animal origin of infection. To the best of our knowledge, this is the first reported case of bacteremia caused by E. rhusiopathiae serotype 6 in humans. Spa typing through sequence analysis may provide variable information for identifying the infection source. E. rhusiopathiae carrying the SpaB gene should be considered in immunosuppressed patients, regardless of animal exposure history. Further studies are needed to elucidate the epidemiological distribution of serotypes among human clinical isolates.